2024
DOI: 10.1007/s00702-024-02749-3
|View full text |Cite
|
Sign up to set email alerts
|

Multi-target drugs for the treatment of cognitive impairment and fatigue in post-COVID syndrome: focus on Ginkgo biloba and Rhodiola rosea

Juliane K. Mueller,
Walter E. Müller

Abstract: Cognitive impairment, depression and (mental) fatigue represent the most frequent neuropsychiatric symptoms of the post-COVID syndrome. Neuroinflammation, oxidative stress and mitochondrial dysfunction have been identified as common pathophysiological mechanisms underlying these symptoms. Attempts to treat post-COVID-associated cognitive impairment and fatigue with different drugs available for other diseases have not yet been successful. One probable explanation could be that these drugs work by one specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 95 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…Most published nonclinical and clinical studies investigating Ginkgo biloba extract were done using the proprietary Ginkgo biloba leaves extract EGb 761 ® . EGb 761 ® was shown to display multimodal effects on a variety of pathogenetic processes which may be involved in PCS ( Mueller and Muller, 2024 ). Flavonoids, terpenoids, and anthocyanidins exhibit neuroprotective effects by modulating signaling pathways known to be impacted by COVID-19 ( Zaa et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most published nonclinical and clinical studies investigating Ginkgo biloba extract were done using the proprietary Ginkgo biloba leaves extract EGb 761 ® . EGb 761 ® was shown to display multimodal effects on a variety of pathogenetic processes which may be involved in PCS ( Mueller and Muller, 2024 ). Flavonoids, terpenoids, and anthocyanidins exhibit neuroprotective effects by modulating signaling pathways known to be impacted by COVID-19 ( Zaa et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis of seven randomized, placebo-controlled trials in patients with dementia showed that treatment-associated risks (relative risk of adverse events, rates of premature withdrawal) in patients taking EGb 761 ® did not differ noticeably compared to the placebo group and confirmed the safety and tolerability of this extract ( Gauthier and Schlaefke, 2014 ). However, even if these pharmacological and clinical results are promising, the available data are still preliminary and require additional proof by further studies ( Mueller and Muller, 2024 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, GB extract (GBE) has a broad pharmacological spectrum for preventing oxidative stress, which protects the central nervous system from depressive processes, improves aspects of impaired neuroplasticity, and increases cellular mitochondrial function (Figure 2). Secondarily, GBE's antioxidant and anti-inflammatory properties improve the prognosis of cardiovascular diseases [158][159][160][161].…”
Section: Ginkgo Biloba and Antioxidant Effectsmentioning
confidence: 99%
“…Similarly, GB extract (GBE) has a broad pharmacological spectrum for preventing oxidative stress, which protects the central nervous system from depressive processes, improves aspects of impaired neuroplasticity, and increases cellular mitochondrial function ( Figure 2 and Figure 6 ). Secondarily, GBE’s antioxidant and anti-inflammatory properties improve the prognosis of cardiovascular diseases [ 161 , 162 , 163 , 164 ].…”
Section: Ginkgo Biloba and Health Effectsmentioning
confidence: 99%